Grau de comprometimento e tempo de trânsito orofaríngeo em disfagia no acidente vascular encefálico - Dallaqua, Rarissa Rúbia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The scales of severity oropharyngeal dysphagia neurogenic, including stroke, prioritize laryngeal penetration and aspiration laryngotracheal as markers. However, oropharyngeal dysphagia in this population have found wide variation in oral and pharyngeal transit times swallowing, and these parameters can also involve, respectively, the nutritional status and safety of the lower airway in post-stroke individuals. The aim of this was to associate the total oral transit time, pharyngeal response and pharyngeal transit time with the severity oropharyngeal dysphagia scale in stroke. Cross-sectional clinical study. The study included 61 subjects after ischemic stroke, independent of the injured hemisphere. The data were recorded one to 30 days after the ictus. Of these, 28 were males and 33 females, with ages ranging from 40 to 101 years (mean 65 years). Videofluoroscopy with specific software developed to measure the time of oral and pharyngeal transit was applied in patients receiving 5 ml of paste bolus. It was measured the total oral transit time (TOTT), response pharyngeal (RPT), and pharyngeal transit (PTT). The subjects were divided into two groups TOTT, RPT PTT and analyzed . The first group ( G1a ) consisted of patients who presented TOTT to 2000 ms and group 1b ( G1b ) individuals who had greater than 2000 ms TOTT . The second group ( G2a ) was composed of individuals who had TRF up to 250 ms and group 2b ( G2b ) subjects who had greater than 250 ms.The 3a ( G3a ) TRF group was composed of individuals who had PTT to 1000 ms and group 3b ( G3b ) subjects who had greater than 1000 ms PTT. At the end of the quantitative analysis was applied of severity oropharyngeal dysphagia proposed by Daniels et al. 1997. The results showed no significant association between total oral transit time, response pharyngeal and pharyngeal transit with severity oropharyngeal dysphagia respectively. When it was analysed between the normal and altered 18...

As escalas de grau de comprometimento para disfagias orofaríngeas neurogênicas, incluindo o Acidente Vascular Encefálico (AVE), priorizam a penetração laríngea e a aspiração laringotraqueal como marcadores. No entanto, as disfagias orofaríngeas encontradas nesta população possuem ampla variação nos tempos de trânsito oral e faríngeo da deglutição, sendo que estes parâmetros também podem comprometer, respectivamente, o quadro nutricional e a segurança pulmonar no indivíduo pós-AVE. Portanto, este estudo teve por objetivo associar os tempos de trânsito oral total, resposta faríngea e trânsito faríngeo com a classificação de grau de comprometimento da disfagia orofaríngea no AVE. Estudo clínico transversal. Foram analisados 61 exames de videofluoroscopia de deglutição de indivíduos após AVE isquêmico, independente do hemisfério lesionado, o ictus variou de 0 a 30 dias (com mediana de 8 dias). Destes, 28 eram do gênero masculino e 33 do gênero feminino, com faixa etária variando de 40 a 101 anos (média de 65 anos). Foi utilizada videofluoroscopia da deglutição e software específico para medir o tempo de deslocamento do bolo alimentar pela fase oral e faríngea da deglutição, por meio de análise quantitativa dos tempos da deglutição. Cada indivíduo foi observado durante a deglutição de 5ml de alimento na consistência pastosa fina. Para este estudo foram analisados três parâmetros, o tempo de trânsito oral total (TTOT), tempo de resposta faríngea (TRF) e tempo de trânsito faríngeo (TTF). Os indivíduos foram divididos baseados na normalidade de cada tempo estudado. O grupo 1a (G1a) foi composto pelos indivíduos que apresentaram TTOT até 2000 ms e grupo 1b (G1b) indivíduos que apresentaram TTOT maior que 2000 ms. O grupo 2a (G2a) foi composto pelos indivíduos que apresentaram TRF até 250 ms e grupo 2b (G2b) indivíduos que apresentaram TRF 16 maior que 250 ms.O grupo 3a (G3a) foi composto...
Keywords: Disturbios da deglutição; Videofluoroscopia; Acidente vascular cerebral; Pesquisa quantitativa; Fonoaudiologia; Cerebrovascular disease